STRATEGI CHINA UNTUK MENCAPAI KEPENTINGAN EKONOMI POLITIK DALAM MEWUJUDKAN ASEAN-CHINA FREE TRADE AREA (ACFTA) - , Yudho Yudistiro, Dra. Siti Daulah Khoiriati, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ASEAN-China Free Trade Area or written with the title ACFTA in this research is a form of regional cooperation with ASEAN China Among the prevailing officially began January 1, 2010. in general, this partnership aims to increase trade volume of both parties